Do baseline estrogen and testosterone affect lower urinary tract symptoms (LUTS) prior to or after pharmacologic treatment with tadalafil?. (9th October 2015) - Egan, K. B.; Miner, M. M.; Suh, M.; McVary, K.; Ni, X.; Roehrborn, C. G.; Wittert, G.; Wong, D. G.; Rosen, R. C.
Summary: Little is known about how total testosterone and estradiol‐17β influence lower urinary tract symptoms (LUTS) in men with benign prostatic hypertrophy (BPH). We analyzed data from a subset of men aged ≥18 years randomized to tadalafil 5 mg once‐daily or placebo who had ≥6 month history of LUTS and an International Prostate Symptom Score (IPSS)≥13 enrolled in one of three randomized, placebo‐controlled tadalafil clinical trials ( N = 958). Three specific aims were addressed, as follows: (i) To characterize enrolled men by treatment randomization and testosterone level; (ii) to assess cross‐sectional associations of estradiol‐17β, testosterone, and LUTS prior to treatment with tadalafil; and, (iii) to assess longitudinal associations between baseline estradiol‐17β and testosterone and improvements or worsening of LUTS during a 12‐week period of tadalafil or placebo administration. LUTS were assessed by total IPSS, IPSS voiding sub‐score (IPSS‐V) and IPSS storage sub‐score (IPSS‐S) for cross‐sectional analyses, and change in total IPSS (ΔIPSS), ΔIPSS‐V, and ΔIPSS‐S between baseline and 12‐week visit for longitudinal analyses. Correlation analyses and linear regression examined associations. Baseline testosterone was not significantly associated with IPSS. In contrast, estradiol‐17β was inversely correlated with IPSS ( r = −0.08; p < 0.05) and IPSS‐S ( r = −0.14; p < 0.05). Tadalafil treatment resulted in greater IPSS improvements in men with lower baseline estradiol‐17β versus those with higher baseline estradiol‐17β. Lower baseline estradiol‐17β was significantly associated with modestly improved ΔIPSS‐V ( p = 0.04) and Δtotal IPSS ( p = 0.05) but not with ΔIPSS‐S, following treatment which may substantiate the role of bladder dysfunction because of nerve and smooth muscle changes in the bladder in addition to benign prostatic enlargement in LUTS. Circulating baseline testosterone did not predict ΔIPSS. Men with lower baseline estradiol‐17β levels showed greater responsiveness to tadalafil 5 mg treatment than those with higher baseline estradiol‐17β levels when responsiveness was measured using total IPSS and IPSS‐V.